The Effect of Teaching Strategies and Curiosity on Students’ Achievement in Reading Comprehension - Sri Astuti; Lince Sihombing; Berlin Sibarani (LINGUISTIK TERAPAN, 2015)
The objectives of this study are to investigate whether: (1) students’ achievement in reading comprehension taught by using Problem-Based Learning stretegy is higher than students’ achievement in reading comprehension by using Reciprocal Teaching strategy, (2) reading comprehension achievement of high curiosity students is higher than reading comprehension achievement of low curiosity students, and (3) there is significant interaction between teaching stretegies and students’ curiosity on students’ reading comprehension achievement. An experimental research with factorial design 2x2 was used in this research. There were 120 students from 2012/2013 Academic Year of SMA BUDI AGUNG Medan as sample of this research. The result reveals that (1) students’ achievement in reading comprehension taught by using Problem-Based Learning stategy is higher than that of taught by using Reciprocal Teaching strategy, (2) reading comprehension achievement of high curiosity is higher than reading comprehension achievement of low curiosity, (3) there is signnificance interaction between teaching strategies and curiosity on students’ achievement in reading comprehension. After the Tukey test was applied, it showed that students have high curiosity got higher result if they were taught by using Problem-Based Learning strategy, and students have low curiosity got higher result if they taught by using Reciprocal Teaching strategy. Keywords: Reading comprehension, Problem-Based Learning, Reciprocal Teaching                     Curiosity